A robust single device MOSFET series resistance extraction method considering horizontal-field-dependent mobility. (1st May 2022) - Takeuchi, Kiyoshi; Mizutani, Tomoko; Saraya, Takuya; Kobayashi, Masaharu; Hiramoto, Toshiro
Abstract: A simple MOSFET series resistance extraction method using multiple drain current versus gate voltage curves of a single device is proposed, where mobility modulation by a horizontal electric field (i.e., weak velocity saturation) is taken into account. The method is validated using TCAD, where series resistance determined from internal potential distributions was used as a reliable reference. Measurement results were also obtained which further support the validity of the method.